666.3:538.94:523.3-7 RESISTANCE AND VOLTAGE ANOMALIES ABOVE 200K BSCCO SYNTHESIZED BY SOLAR TECHNOLOGY. - Bobokulov, Sirojiddin; Eshonkulov, Elyor; Gulamova, Dilbara (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The purpose of the research is to obtain room temperature superconducting phases in ceramics based on bismuth cuprates using solar technology. The synthesis of BSCCO was carried out using the “Solar Fast Alloys Quenchig” technology at the Big Solar Furnace (Parkent). Based on the results of microstructural and X-ray methods, the glass-crystalline composition of the precursors and the homo-phase composition of the nanolayered ceramics were determined. Resistance anomalies in the temperature range of 280-320 K have been established, interpreted in the assumption of room temperature superconducting phases. The Meissner effect in BSCCO precursors and ceramics under daylight and under the influence of light at room temperature and normal atmospheric pressure has been established. Resistance anomalies, the Meisner effect in the assumption of room temperature phases, are explained by the influence of the solar spectrum and technological conditions on the electronic structure of atoms. Different oxygen stoichiometry of homologous phases determines different potentials of adjacent layers, resulting in charge transport and increased charge density at intergranular boundaries.